Assessing Interactive Online Communication and Its Effect on Public Relations Outcomes with Insight from Selected Banks. - Mensah-Aborampah, Mabel (UniMAC - GIJ, 2021)
The study assessed how organizations in the banking industry use interactive online communication enabled by technology to achieve overall organizational success through their public relations efforts. In order to achieve this, the interactive online communication channels of GCB Bank and Fidelity Bank were investigated to ascertain how they use interactive online communication in their practice and to find out if these channels have been effective tool for the banks. By employing a mixed method approach, data was collected from 100 customers of GCB Bank and Fidelity Bank. This afforded the study to use the survey approach while employing non-probability sampling technique. The findings showed that the channels mostly used by respondents included face-to-face interactions, USSD, social media and through emails. It was also realized that interactive online communication affected respondents’ perception of their bank positively. As a recommendation, the study proposed that banks as well as other corporate organizations invest in adopting interactive communication as part of its communication strategy.
THESIS